Mother's Behavior, Family Income and Availability of Iodized Salt in the Household - Muhammad Saleh; Intje Picauly; Ina Debora Ratu Ludji (Health Notions, 2018)
Iodine is one of the essential micro minerals needed by human body in small amounts. As a result of iodine deficiency disorder is often found in mountainous areas, deficiency of iodine in the body provide hypothyroidisim conditions by increasing thyroid tissue. The aim of this study was to analyze the relationship between the behavior of housewives about the availability of iodized salt. This type of research is analytic observational with cross sectional approach. The population in this study were all family heads in the Taninin Village area, Takari District, Kupang Regency, NTT Province, Indonesia. The sample size studied was 85 families selected randomly. Independent variables in this study are: 1) housewife behavior which includes: knowledge, attitudes, actions related to the use of iodized salt, 2) family income. While the dependent variable is the availability of iodized salt in the household. Data was collected through filling out questionnaires. The data that has been collected is categorical so that it is presented in the form of frequencies equipped with percentages. Further hypothesis testing using Chi square test for the first stage and continued with multiple logistic regression tests for the second stage. Referring to the logistic regression model produced, the factors that influence the availability of iodized salt in the household are maternal knowledge. The probability of availability of iodized salt due to maternal knowledge is 2.107, which means that 1 time the increase in the respondent's knowledge of iodized salt will increase the availability of iodized salt by 2.1 times greaterKeywords: Knowledge, Iodized salt